2012
DOI: 10.2466/16.13.17.pr0.110.3.791-800
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Domestic Violence and Identity Development among Adolescent University Students in South Africa

Abstract: Summary.-This study examined the relationship between exposure to domestic violence and identity development in a sample of 108 undergraduate students with an average age of 18.7 yr. from University of Limpopo in South Africa. There were more women (n=64; 58.7%) in the study than men (n=45; 41.3%). Adolescents were classified into high and low domestic violence exposure groups on the basis of a median split in physical violence scores from the Child Exposure to Domestic Violence Scale (CEDV). Exposure was then… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Two of these studies reported emotional maltreatment that occurred in childhood to be a key factor in the development of an impaired self-identity in contrast to noninterpersonal trauma and adult maltreatment (Briere & Rickards, 2007; of moderate quality, 69%) and a history of CSA to be significantly associated with negative self-identity based on a sample of American university students (Lopez & Heffer, 1998; of high quality, 83.3%). A further three studies based on university samples also reported a history of maltreatment or exposure to domestic abuse to be associated with greater impairments of self-identity and cognitive schemas about the self (in a female-only sample; Alexander & Lupfer, 1987; of lower quality, 47.6%; and two mixed-sex samples; Makhubela, 2012; of moderate quality, 69% Ponce et al, 2004; also of moderate quality, 71.4%).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Two of these studies reported emotional maltreatment that occurred in childhood to be a key factor in the development of an impaired self-identity in contrast to noninterpersonal trauma and adult maltreatment (Briere & Rickards, 2007; of moderate quality, 69%) and a history of CSA to be significantly associated with negative self-identity based on a sample of American university students (Lopez & Heffer, 1998; of high quality, 83.3%). A further three studies based on university samples also reported a history of maltreatment or exposure to domestic abuse to be associated with greater impairments of self-identity and cognitive schemas about the self (in a female-only sample; Alexander & Lupfer, 1987; of lower quality, 47.6%; and two mixed-sex samples; Makhubela, 2012; of moderate quality, 69% Ponce et al, 2004; also of moderate quality, 71.4%).…”
Section: Resultsmentioning
confidence: 99%
“…Approximately half of the studies (53%) comprised an all-female sample, with the remaining studies being an all-male sample (Ray, 1997) or a mixed sample ranging from 27% to 90% female participants. The age range across studies varied from 5 to 91 years, with over half the studies being predominantly derived from a child and/or adolescent sample (for example, 5–19 years; N = 30, 51%; Allen & Tarnowski, 1989; Deb & Mukherjee, 2009; Deb et al, 2016; Esparza & Esperat, 1996; German et al, 1990; Kinard, 1980; Mannarino et al, 1994, 1989, 1991; Mennen, 1994; Mernen & Meadow, 1994; Milan & Pinderhughes, 2000; Mota & Matos, 2015; Oates et al, 1985; Oates et al, 1994; Orr & Downes, 1985; Reyes, 2008; Reyes et al, 1996; Riesen & Porath, 2004; Rogosch & Cicchetti, 2005; Runyon et al, 2009; Rust & Troupe, 1991; Silva & Calheiros, 2020; Simmons & Weinman, 1991; Solomon & Serres, 1999; Stern et al, 1995; Stovall & Craig, 1990; Tong et al, 1987; Trickett et al, 2001; Wonderlich et al, 2001); followed by adult samples (for example, 17–91 years; N = 27, 46%; Alexander & Lupfer, 1987; Brayden et al, 1995; Briere & Rickards, 2007; Classen et al, 1998; Clifford et al, 2020a,’ 2020b; Dimmitt, 1995a,’ 1995b; Hoagwood, 1990; Kandeğer & Naziroğlu, 2021; Keshet & Gilboa-Schechtman, 2017, 2019; Krause & Roth, 2011; Lopez & Heffer, 1998; Makhubela, 2012; McAlpine & Shanks, 2010; Murthi et al, 2006; Nixon & Nishith, 2005; Overstreet et al, 2017; Ponce et al, 2004; Ray, 1997; Steinberg et al, 2003; Thompson-Hollands et al, 2017; Van Buren & Weierich, 2015; Vartanian et al, 2016; 2018; Whealin & Jackson, 2002), and two studies (3%) were mixed pediatric/adult age samples (Alboebadi et al, 2015; Oates et al, 1998).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Adsorption in continuous stirred tank reactors (CSTRs) under the names of RIP and CIP has become an established process for extraction of gold and uranium, , and, recently, zinc, copper, nickel, and cobalt. One of the most applied adsorption model in resin-in-pulp (RIP) and carbon-in-pulp (CIP) processes when intraparticle mass-transfer resistance prevails is the Boyd’s series model.…”
Section: Discussionmentioning
confidence: 99%